Carbon ion radiotherapy of human lung cancer attenuates HIF‐1 signaling and acts with considerably enhanced therapeutic efficiency. Issue 3 (17th December 2013) - Subtil, Florentine S. B.; Wilhelm, Jochen; Bill, Verena; Westholt, Niklas; Rudolph, Susann; Fischer, Julia; Scheel, Sebastian; Seay, Ulrike; Fournier, Claudia; Taucher‐Scholz, Gisela; Scholz, Michael; Seeger, Werner; et al.
Abstract : Carbon ion irradiation is an emerging therapeutic option for various tumor entities. Radiation resistance of solid tumors toward photon irradiation is caused by attenuation of DNA damage in less oxygenated tumor areas and by increased hypoxia‐inducible factor (HIF)‐1 signaling. Carbon ion irradiation acts independently of oxygen;however, the role of HIF‐1 is unclear. We analyzed the effect of HIF‐1 signaling after carbon ions in comparison to photons by using biological equivalent radiation doses in a human non‐small‐cell cancer model. The studies were performed in cultured A549 and H1299 cell lines and in A549 xenografts. Knockdown of HIF‐1α in vivo combined with photon irradiation delayed tumor growth (23 vs. 13 d; P <0.05). Photon irradiation induced HIF‐1α and target genes, predominantly in oxygenated cells (1.6‐fold; P <0.05), with subsequent enhanced tumor angiogenesis (1.7‐fold; P <0.05). These effects were not observed after carbon ion irradiation. Micro‐DNA array analysis indicated that photons, but not carbon ions, significantly induced components of the mTOR (mammalian target of rapamycin) pathway (gene set enrichment analysis; P <0.01) as relevant for HIF‐1α induction. After carbon ion irradiation in vivo, we observed substantially decreased HIF‐1α levels (8.9‐fold; P <0.01) and drastically delayed tumor growth ( P <0.01), an important finding that indicates a higher relative biological effectiveness (RBE) than anticipated from the cell survival data. Taken together, the evidence showed that carbon ions mediate an improved therapeutic effectiveness without tumor‐promoting HIF‐1 signaling.—Subtil, F. S. B., Wilhelm, J., Bill, V., Westholt, N., Rudolph, S., Fischer, J., Scheel, S., Seay, U., Fournier, C., Taucher‐Scholz, G., Scholz, M., Seeger, W., Engenhart‐Cabillic, R., Rose, F., Dahm‐Daphi, J., Hänze, J. Carbon ion radiotherapy of human lung cancer attenuates HIF‐1 signaling and acts with considerably enhanced therapeutic efficiency. FASEB J. 28, 1412–1421 (2014). www.fasebj.org